Rural-to-urban migration, socio-economic status and cardiovascular diseases risk factors among Bangladeshi adults: A nationwide population based survey - Mumu, Shirin Jahan; Stanaway, Fiona F.; Merom, Dafna (Frontiers in Public Health, 2023)
Background: Rural-to-urban migration is one of the key drivers of urbanization in Bangladesh and may impact on cardiovascular diseases (CVD) risk due to lifestyle changes. This study examined whether CVD risk factors were associated with migration to and duration of urban life, considering socio-economic indicators. Methods: A total of 27,792 participants (18-59 years) from the 2006 Bangladesh cross-sectional Urban Health Survey were included in the analyses of whom 14,167 (M: 7278; W: 6889) were non-migrant urban residents and 13,625 (M: 6413; W: 7212) were rural-to-urban migrants. Gender-specific prevalence of CVD risk factors were estimated for urban and migrant groups. Multivariate logistic regression models were used to test the association between each CVD risk by education and wealth within each study group and their possible effect modification. An analysis on the rural-to-urban migrant subgroup only was conducted to examine the association between each CVD risk factor and length of urban stay adjusted for demographic and socio-economic indicators. Results: Compared to urban residents, migrants had significantly lower prevalence of overweight/obesity for both genders. Hypertension was higher among urban women while alcohol/illicit drug use was higher among urban men. Mental health disorders were higher among migrants than urban residents for both genders and no difference were noted for diabetes or cigarette smoking prevalence. In both study groups and genders, the risk of overweight/obesity, hypertension and diabetes increased with increasing education and wealth whereas for mental health disorders, alcohol/illicit drug use, cigarette and bidi smoking the reverse was found. Differences in BMI between migrant and urban women were attenuated with increased education levels (p=0.014 for interaction). Consistent increasing pattern of risk was observed with longer duration of urban stay; in migrant men for obesity (OR=1.67), smoking (OR=1.67) and alcohol/illicit drug use (OR=2.86), and for obesity and mental health disorder among migrant women. Conclusions: Migrants had high proportion of CVD risk factors which were influenced by education, wealth and duration of urban stay.